Optimalisasi Penggunaan Chromebook Sebagai Upaya Guru dalam Meningkatkan Antusiasme Belajar Siswa Kelas V - Nanda Amelia; Agung Setyawan; Sih Widayati; Nurhalima (maktab: Jurnal Pendidikan dan Teknologi, 2024)
The Ministry of Education and Culture facilitates all schools in remote areas of the country by providing Chromebooks. This research was conducted with the aim of finding out how to optimize the use of Chromebooks at school and the response of class v students at UPTD SDN Tanjung Jati 2 after using Chromebooks during learning activities. This research is qualitative research with data collection techniques through interviews and observation. Data processing was carried out using qualitative descriptive analysis. The research results show that Chromebooks are used optimally by students at school. Through teacher guidance, students can make optimal use of the Google Docs, YouTube and Google Translate applications. Google Docs is used by students in learning activities to record material and important things they have learned previously. YouTube is used by students to watch animated learning videos. Meanwhile, Google Translate is usually used by students to obtain English translations when learning English. Based on observations, learning using Chromebooks can actually increase students' enthusiasm for learning. This is shown by students' responses who are very enthusiastic about learning, actively ask and answer questions, and dare to express opinions.